The influence of individual factors, transfer climate, and training design on training transfer: the mediating role of motivation to transfer / Sharrifah Ali - Ali, Sharrifah (2016)
Both organizations and employees in recent decades have increasingly focused their attention on lifelong and continuous training. This phenomenon is strongly related to the extension of working life which leads to socio-economical effects and new challenges for employees specifically in knowledge, skills, and attitudes (KSA). In order to improve employees' KSA, and to create an intellectual capital that perfectly fits the organization's culture, most organizations provide learning opportunities (training) to their employees. Although training is not the only way for employees' learning to occur, the investment made in training requires an analysis of certain evidence to determine if, indeed, training pays off in organizational effectiveness. Specifically, training alone will do little to increase employees or organizational performance unless what is learned as a result of training is transferred into on-the-job behaviour. Review of related international literatures revealed the importance of training transfer, nevertheless, there is lack of empirical evidence to support this in the Malaysian context and this study contributes a deeper understanding of some of the critical aspects of training transfer. Using a research framework constructed from an adaptation of two key training evaluation models: Training Transfer Process (Baldwin & Ford, 1998), and Kirkpatrick's Training Evaluation Model - Level 3 (1994), this study explores the argument that motivation to transfer and training transfer are influenced by training transfer determinants (individual factors, transfer climate, and training design). In particular, this study seeks to investigate the role of motivation to transfer in a relationship between training transfer determinants and training transfer. Thus, it presents and discusses empirical findings from a data collected using administered self-reported survey instrument from 286 support staff of University Teknologi MARA applying Structural Equation Modeling (AMOS Version 20) and Statistical Package for Social Science (SPSS Version 20). The data was analyzed adopting two-step model-building approach of SEM - Measurement Model, and Structural Model. In checking the model fit, Chi-square (ᵪ²), Goodness-of-Fit (GFI), Comparative Fit Index (CFI), Tucker-Lewis Index (TLI), and Root Mean Square Error of Approximation (RMSEA) were performed. Findings of this study indicated that Performance Self-Efficacy, Opportunity to Use, and Transfer Design support the mediating role of motivation to transfer which indicates a final model with acceptable level of Goodness-of-Fit: GFI = .812, CFI = .939, TLI = .934, and RMSEA = .046. This study represents a more accurate methodological process, attempting to clearly define each of the underlying constructs. Assessments of the reliabilities and validities of each construct using Confirmatory Factor Analysis (CFA) strengthen the correspondence rules between both empirical and theoretical concepts. Results of this study signify that training practitioners must consider how to optimize trainees' interest and motivation to transfer prior to training to ensure learning effectiveness and the transfer of training in post-training stage. Hence, management should discover training strategies and instructional techniques that can be utilized to maximize the degree to which classroom learning matches and concepts practiced related to real life situations on the job. Finally, there is also a necessity for the organizations to formalize the goal-setting procedures and the follow-up programs in ensuring the transfer of training to workplace is successful.